Surfactants at environmentally relevant concentrations interfere the inducible defense of Scenedesmus obliquus and the implications for ecological risk assessment. (June 2020) - Zhu, Xuexia; Wang, Zeshuang; Sun, Yunfei; Gu, Lei; Zhang, Lu; Wang, Jun; Huang, Yuan; Yang, Zhou
Abstract: The ecotoxicology of surfactants is attracting wide attention due to the rapidly expanding global application. As interspecific relationships play one of the central roles in structuring biological communities, it is necessary to take it into risk assessments on surfactants. With this aim, our study investigated the interference of three common surfactants on the inducible defense of a freshwater phytoplankton Scenedesmus obliquus . Nonlethal environmentally relevant concentrations (10 and 100 μg L −1 ) of several surfactants were set up. Results showed that growth and photosynthetic efficiency of Scenedesmus were inhibited during first 96 h, but recovered in the later stage. Surfactants interfered inducible defense of Scenedesmus against Daphnia grazing, and the interference was related to chemical characteristics of surfactants. The anionic surfactant sodium dodecyl sulfate (SDS) enhanced the colony formation even without grazing cues, whereas fewer defensive colonies were formed under the effects of cationic surfactant benzalkonium bromide (BZK) and nonionic surfactant polyoxyethylene (40) nonylphenol ether (NPE). These findings highlighted the sensitivity of grazer-induced morphological defense of Scenedesmus to surfactants even at nonlethal concentrations, which potentially affects the energy and information flow between trophic levels. This study appeals for more attention to take interspecific relationships into consideration in assessing the potential ecological risk of pollutants. Graphical abstract: Image 1 Highlights: Environmentally relevant levels of surfactants cause acute toxicity to S. obliquus. Changes of Fv /Fm and ΦPSII reflect the impairment and recovery of photosystem. Anionic surfactant SDS enhances the colony formation in S. obliquus. Cationic and nonionic surfactants (BZK, NPE) impair the inducible defense. Interference on defense is more ecologically significant than growth inhibition. Abstract : Surfactants with different characteristics at environmentally relevant concentrations differently interfere the grazing-induced morphological defense of Scenedesmus .